Disentangling the mental health impact of childhood abuse and neglect. (January 2017) - Cecil, Charlotte A.M.; Viding, Essi; Fearon, Pasco; Glaser, Danya; McCrory, Eamon J.
Abstract: It is unclear whether maltreatment types exert common or specific effects on mental health. In the current study, we aimed to systematically characterize the unique, shared and cumulative effects of maltreatment types on psychiatric symptoms, using data drawn from a community sample of high-risk youth ( n = 204, M = 18.85). Analyses controlled for a range of potentially confounding variables, including socio-demographic variables, neighbourhood deprivation and levels of community violence exposure. Outcome measures included multi-informant reports of internalizing difficulties, as well as data on externalizing problems and trauma-related symptoms. We found that (i) consistent with previous studies, maltreatment types were highly interrelated and frequently co-occurred; (ii) symptom severity linearly increased with the number of maltreatment types experienced (more so for self-report vs informant ratings); and (iii) while most forms of maltreatment were significantly associated with mental health outcomes when examined individually, few unique effects were observed when modelling maltreatment types simultaneously, pointing to an important role of shared variance in driving maltreatment effects on mental health. Emotional abuse emerged as the main independent predictor of psychiatric symptomatology – over and above other maltreatment types – and this effect was comparable for males and females (i.e. no significant interaction with sex). Findings contribute to a better understanding of heterogeneity in individual responses to maltreatment.